Drugs in Pregnancy and Lactation: a reference guide to fetal and neonatal risk - Briggs, G.G.; Towers, C.V.; Forinash, A.B. (Wolters Kluwer, 2021)
This volume provides practical and up-to-date information on more than 1000 drugs for health professionals caring for pregnant and lactating women
osc 25/10/2022
Keywords: Foetus - effects of drugs; Breast milk - contamination; Pregnancy - complications